Work Engagement: Psychological Well-Being dan Perceived Organizational Support Perawat di Daerah 3T - Taneu, Novita; Sari, Rr Erita Yuliasesti Diah (Psyche 165 Journal, 2023)
Nurses are one of the health professions that have a big responsibility in providing care and treatment to patients. However, the success of the nursing profession is inseparable from the level of work engagement of nurses towards the profession they are engaged in. Work engagement is a concept that describes the extent to which an employee feels attached to his job, the organization where they work, and the personal satisfaction he feels from his job. This study aims to examine the effect of psychological well-being and perceived organizational support on the work engagement of nurses at puskesmas with ASN status in the 3T area of X District, East Indonesia. The population in this study were puskesmas nurses who worked in X District, Eastern Indonesia with ASN status. The sampling technique used was purposive sampling. The measurement tool used consists of three scales, namely the work engagement scale, the perceived organizational support scale and the psychological well-being scale. The analysis technique used in this study uses multiple linear analysis. The results of the analysis show a value of p = 0.000 (p <0.01), which indicates that psychological well-being and perceived organizational support can very significantly affect work engagement. The first minor hypothesis test has a significance value of 0.000 <0.01, which means that psychological well-being has a positive and very significant effect on work engagement. The results of the second minor hypothesis test have a significance value of 0.003 <0.01, meaning that perceived organizational support has a positive and very significant effect on work engagement. These findings indicate that when the psychological well-being of nurses is in good condition, the level of work engagement they have will also be good.